2009
DOI: 10.1007/s00467-009-1192-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone treatment of infants with chronic kidney disease: requirement, efficacy, and safety

Abstract: Growth failure is still a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
6
0
6
Order By: Relevance
“…Catch-up growth is not noted. A late onset and short duration of puberty result in a further important loss of height SDS during the pubertal growth phase [57,58].…”
Section: Growth Hormone Therapymentioning
confidence: 99%
“…Catch-up growth is not noted. A late onset and short duration of puberty result in a further important loss of height SDS during the pubertal growth phase [57,58].…”
Section: Growth Hormone Therapymentioning
confidence: 99%
“…Additionally, sustaining adequate nutrition is further hampered as this patient group tend to suffer catabolic phases related to infectious episodes, recurrent vomiting secondary to gastro-oesophageal reflux, chronic dehydration [6] and uraemic effects upon gut motility [7]. Nevertheless, Kari et al [8] have demonstrated excellent growth in this patient group with early enteral feeding via nasogastric or gastrostomy tubes.…”
Section: Growth and Pth Through The Phasesmentioning
confidence: 94%
“…La introducción de terapias derivadas de la medicina génica permite hoy en día que en la mayoría de los casos el paciente urémico en diálisis no sea diferente de sus pares, y que el período de su vida en que se someten a diálisis peritoneal o hemodiálisis, en espera de un trasplante renal, sea compatible con una vida normal. La introducción de sistemas automatizados de diálisis peritoneal como la Home Choice® (Baxter Healthcare Co), la eritropoyetina humana recombinante (EPO) de vida media corta, mediana y prolongada, la 1,25 (OH) 2 VitD o calcitriol, medicamentos fi jadores de fósforo intestinal, calcimiméticos y fi nalmente la hormona de crecimiento (GH), son la base de un tratamiento médico altamente favorable durante el período en diálisis [4][5][6][7][8] .…”
Section: Introductionunclassified